Trends in IgG Antibody Levels in Covid-19 Patients in Different Clinical Manifestations in Bengkulu City: Cohort Study - Debie Rizqoh; Enny Nugrahaeni; Mulya Sundari; Dessy Triana; Mardhatillah Sariyanti; Nikki Aldi Massardi (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2022)
More than two years have lasted since the coronavirus disease 2019 (Covid-19) pandemic. The case of Covid-19 in Indonesia has spread to all provinces and areas such as Bengkulu City. This study aims to determine the profile of clinical manifestations and antibody dynamics in Covid-19 patients in Bengkulu City. This study used a cohort design on Covid-19 patients at two Bengkulu City referral hospitals, M. Yunus Hospital and Harapan dan Doa Hospital. Data on clinical manifestations were obtained from the medical records of Covid-19 patients. Meanwhile, to determine the level of IgM and IgG antibodies, patient serum samples were taken directly from respondents from the beginning of hospital admission three times on the 1st, 2nd and 3rd weeks. Then the samples were examined by immunofluorescent assay method. The results of this study indicate that, in general, there are no significant differences in anti-SARS-CoV-2 IgG levels in Covid-19 patients in the 1st, 2nd and 3rd weeks of Covid-19 in Bengkulu City. The Spearman correlation test also showed no correlation between IgG levels and the clinical manifestations of Covid-19. Although not statistically significant, there was a trend towards differences in antibody levels in patients with mild, moderate and severe clinical manifestations. The results of this study indicate that there are variations in antibody dynamics in Covid-19 patients in Bengkulu City.